EXPERIMENTAL EVALUATION OF SOLAR COLLECTORS - Leite, Newton G. C.; Reis, Luiz Carlos B. S.; Zanardi, Maurício A. (Seven Editora, 2024)
The purpose of the present work was to investigate the association of two important engineering devices, the two-phase thermosyphon and the solar collector. A cycle to obtain high vacuum was set up to manufacture thermosyphons, which were inserted into evacuated glass tubes to compose the structure of a solar collector prototype. The prototype was operated over a period of eight months, during which two other solar collectors were tested simultaneously for comparison purposes. The other two collectors were purchased on the market, one of which already included the thermosyphons, while the other operated without them. Temperature readings were taken at the manifold inlet and outlet, as well as in the main water supply, and in the storage tank. The temperature data were analyzed and could be condensed into just two 24-hour periods, as they showed reproducible behavior. A calorimeter allowed estimating the amount of stored energy, which in this case used twenty 24 hour periods for analysis. It was concluded that the solar collector that uses the thermosyphon can reach higher temperatures at the manifold outlet, but the storage tank can interfere, causing a decrease in the temperature of the water that reaches the consumer. DOI: https://doi.org/10.56238/sevened2024.037-104